2021
DOI: 10.1007/s11356-021-16430-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of plant communities’ influence to grasshopper abundance distribution in heterogeneous landscapes at the upper reaches of Heihe River, Qilian Mountains, China

Abstract: Understanding the impact of the heterogeneity of the ecological environment on biodiversity is a key issue in ecology. Topographical heterogeneity was potentially important in grassland systems to create or change habitats for grasshopper settlement and foraging. Yet, there was little knowledge of how grasshopper communities respond to plant communities along the altitude gradient. We investigated the role of plant communities on grasshopper diversity with geostatistical methods to test the effects of heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Lv et al [44] made predictions about suitable habitats for grasshoppers in the alpine grasslands of the Qilian Mountains. On a small scale, numerous scholars have conducted research on the species composition [2] and quantitative characteristics [18] of grasshoppers in the Qilian Mountains, as well as their relationships with vegetation communities [45], topography [46], temperature, and rainfall [47]. Due to the influence of climatic and topographic conditions, the grassland ecosystem of the Qilian Mountains is complex and diverse, providing varied and suitable habitat conditions for various grasshopper species, making grasshopper control difficult [48].…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al [44] made predictions about suitable habitats for grasshoppers in the alpine grasslands of the Qilian Mountains. On a small scale, numerous scholars have conducted research on the species composition [2] and quantitative characteristics [18] of grasshoppers in the Qilian Mountains, as well as their relationships with vegetation communities [45], topography [46], temperature, and rainfall [47]. Due to the influence of climatic and topographic conditions, the grassland ecosystem of the Qilian Mountains is complex and diverse, providing varied and suitable habitat conditions for various grasshopper species, making grasshopper control difficult [48].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation mainly affects the growth and development of grasshoppers through its effects on soil moisture [ 28 , 29 ]. Altitude and slope are the main topographic factors affecting the distribution of grasshoppers [ 30 , 31 , 32 , 33 , 34 ]. The soil type and soil water content also affect the distribution and densities of grasshoppers [ 28 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies showed that grasshopper occurrence is affected by different environmental factors or geographical attributes [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. For instance, studies focusing on single factors influencing grasshopper occurrence demonstrate that grasshopper occurrence has a high correlation with plants [ 13 ]. Grasshopper occurrence and spatial distribution strongly respond to local vegetation height and amount of bare ground [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The soil type, as well as topsoil moisture content can affect grasshopper occurrence by influencing grasshopper density [ 18 , 20 ]. Moreover, the region-specific topography, mainly including altitude and slope, has clear effects on the distribution of grasshopper occurrence [ 13 , 21 , 22 , 23 , 24 , 25 ]. Several studies on the relationship between the microclimate (mainly including temperature and precipitation) and the distribution of grasshopper occurrence [ 9 , 17 , 25 , 26 , 27 , 28 , 29 , 30 ] exist.…”
Section: Introductionmentioning
confidence: 99%